DESIGN AND CONSTRUCTION OF A WEB-BASED VILLAGE FUND MANAGEMENT REPORTING APPLICATION AT THE SENA VILLAGE OFFICE, DUSUN V - Br Berutu, Ayu Anjelli; Nurjamiyah (Bahasa Indonesia, 2025)
The Deli Serdang Regency Government is located in the Province of North Sumatra, Indonesia. The Village Office of Hamlet V is located on Jalan Batang Kuis Tanjung Morawa, Deli Serdang Regency. Sena Village has X Hamlets, and has Village Officials who are responsible for carrying out village duties and functions. The Sena Village Office of Hamlet V still uses a manual system when conducting Village Fund Management Reports, namely Recording in the Agenda Book. The use of a manual system results in slow processes and potential errors in financial recording. The purpose of this study is to create a Web-Based Village Fund Management Application using the PHP (Hypertext Preprocessor) programming language and the Database used is MySQL (My Structured Query Language). The scope of this study is limited to the development of an information system with login, dashboard, and expenditure report features. The methodology used includes cash basis research methods and prototype development methods. Data were collected through observation, interviews, and literature studies. The results of the study indicate that this application can improve efficiency, effectiveness, and transparency in village fund management. The conclusion of this study is that the application of a web-based information system can facilitate village fund management and improve accountability.